An Analysis of EFL Teacher-Made Tests - Rice Pesiwarissa; Karolis Anaktototy; Hendrik Jacob Maruanaya (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2021)
Teacher-made tests became a common practice in school to assess the students’ mastery of the content knowledge and skills. In the development of the test, multiple-choice test form is frequently a preferred option among the teacher. This study examines the content knowledge, cognitive and authentic evidence of teacher-made multiple-choice tests in EFL learning context in Junior High school. The English midterm-test document for grade 7 as the source of data. The test consists of 25 multiple choice items. The analysis showed that test items functioned primarily at the content knowledge of linguistic competence (52%), discourse competence (24%), and interactional competence (24%). The cognitive functioning level is C1 (4%), C2 (32%), C3 (32%) and C4 (32%), while the authentic functioning level is 16%. However, there are 84% items that are considered less authentic with the result of the analysis showing the mean score of the raters is 2.69. Regarding the findings of this study, the teacher needs to develop the authentic tasks in the test.